Secondary Metabolites and Antioxidant Activity of Ethanolic Extract of Faloak (Sterculia quadrifida) - Dillak, Hory Iramaya; Kristiani, Elizabeth Betty Elok; Kasmiyati, Sri (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Faloak (Sterculia quadrifida) is a medicinal plant used by the people of East Nusa Tenggara to treat lumbago, liver dysfunction and to restore the stamina. The research aims were to determine the qualitative and quantitative content of flavonoids, phenols, and tannins, as well as to examine the antioxidant activity of roots, stem barks, leaves, fruits and seeds extracts of faloak plant. Each organ was extracted with ethanol 70% using the maceration method. The qualitative content of bioactive compounds was determined using the phytochemical screening method. The determination of bioactive compounds concentration was using spectrophotometric methods and antioxidant activity was using the DPPH method. The result of phytochemical screening showed that all of the extracts were exhibit phenols compounds, but the flavonoids and tannins were only found in roots, barks, leaves, and fruits extracts. The quantitative content of total flavonoids of roots, barks, leaves, fruits, and seeds was 48.09; 62.76; 12.56; 11.91 and 1.55 mg/g, while the phenols total content were 82.90; 45.37; 3.43; 29.50 and 2.89 mg/g. Tannins total content were 71.26; 59.64; 10.52; 13.18 and 14.12 mg/g samples respectively. The stem barks and roots extracts showed a very strong antioxidant activity, while leaves, fruits, and seeds extracts belong to the strong category. The potential of faloak as an antioxidant has been widely studied, especially in the stem bark. Studies on the antioxidant activity of roots, leaves, fruits, and seeds can provide new information about the benefits of phaloac plants as a source of natural antioxidants.